Problems in Legalizing Abortion as a Legal Protection for Rape Victims - Ekatama, Noviyanti; Novianto, Widodo Trisno; Purwadi, Hari (Journal of Health Policy and Management, 2019)
Background: Legalization of abortion in Law No. 36 of 2009 is only allowed by two criteria, namely indications of medical emergencies and / or pregnancy due to rape. The act of abortion due to rape can only be done if the gestational age is 40 days at the most, calculated from the first day of the last menstruation. In addition, this legal abortion can only be done by a competent doctor; and by including information from investigators, psychologists, and/or other experts regarding alleged rape. This raises a problem because every doctor adheres to the oath of office attached to each doctor and the period of time given by legislation is considered insufficient to guarantee legal protection for women, especially rape victims. This study aimed to explore problems in legalizing abortion as a legal protection for rape victims.Subjects and Method: This was a normative legal study and refers to the conceptual approach, and the statutory approach. The data were analyzed to give an analytical knife using syllogism deduction by placing two major premises and a minor premise.Results: First, this legal abortion action is in principle contrary to the oath and medical code of ethics which states that each doctor must respect every human life from the moment of conception. Second, related to the period of implementation of legal abortion, Government regulation No. 61 of 2014 provides a period of 40 days calculated from the first day of the last menstruation. The period of time is not enough to determine whether the rape case can be resolved or not because everyone applies a legal principle of the presumption of innocent and it will be very dangerous if the criminal proceedings are continued until the decision has a permanent legal force (inkracht van gewisde) which then states that the crime of rape has not been proven, even though the pregnancy has been carried out an abortion has been carried out by only attaching a certificate of alleged rape.Conclusion: The act of abortion was allowed based on two criteria, namely abortion on the indication of medical emergencies and pregnancy due to rape where the pregnancy would cause psychological trauma for the pregnant womanKeywords: abortion, legalization, rape crime, women's protectionCorrespondence: Noviyanti Ekatama. Masters Program in Law, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java. Email: noviyanti.ekatama@gmail.com. Mobile: +6281391041111.Journal of Health Policy and Management (2019), 4(2): 117-127https://doi.org/10.26911/thejhpm.2019.04.02.07